From green infrastructure to green citizenship: A sustainable city marketing model of place attachment in Jakarta’s urban green spaces - Rury Mulina; Febri Sari Siahaan; Usep Suhud; Setyo Ferry Wibowo; Andrian Haro (Journal of Placemaking and Streetscape Design, 2026)
Background: Urban sustainability is often associated with the provision of green infrastructure, yet the presence of parks, pedestrian areas, and green public spaces does not automatically produce environmentally responsible citizens. This study examines how sustainable city marketing attributes shape Green Citizenship Behavior among users of urban green public spaces in Jakarta. Methods: A quantitative explanatory design was employed using survey data from 250 respondents who had used urban green public spaces in Jakarta within the last six months. The study examined the effects of Sustainable City Branding, Urban Green Space Quality, and Green City Identification on Green Citizenship Behavior, with Place Attachment positioned as a mediating variable. Data were analyzed using Partial Least Squares Structural Equation Modeling through SmartPLS 4. Findings: The results show that Sustainable City Branding, Urban Green Space Quality, and Green City Identification significantly influence Place Attachment. These three variables also have positive and significant direct effects on Green Citizenship Behavior. Place Attachment significantly influences Green Citizenship Behavior and mediates the relationships between Sustainable City Branding, Urban Green Space Quality, Green City Identification, and Green Citizenship Behavior. The strongest effect on Place Attachment is found in Sustainable City Branding, while Green City Identification emerges as the strongest direct predictor of Green Citizenship Behavior among the three sustainable city attributes. Conclusion: The findings indicate that Green Citizenship Behavior is not shaped by green infrastructure alone, but by the interaction between sustainability-oriented city image, green spatial experience, identity alignment, and emotional-functional attachment to place. Novelty/Originality of this article: This study contributes to sustainable marketing literature by reframing the city as a branded and experienced sustainability space and by extending the discussion from product-based green consumption to city-based green citizenship behavior.